Xanthine Oxidase Inhibitory Activity and Chemical Composition of Pistacia chinensis Leaf Essential Oil - Chi-Ya Huang; Yu-Yi Chang; Shang-Tzen Chang; Hui-Ting Chang (MDPI AG, 2022)
Gout is a common metabolic disease caused by abnormal purine metabolism that promotes the formation and deposition of monosodium urate crystals within joints that causes acute arthritis and can seriously affect the daily life of patients. Pistacia chinensis is one of the traditional medicinal plants of the Anacardiaceae family, and there have been many studies on its biological activity, including anti-inflammatory, antidepressant, antibacterial, antioxidant, and hypoglycemic activities. The aim of this study was to evaluate the antigout effect of P. chinensis leaf essential oil and its constituents through xanthine oxidase inhibition. Leaf essential oil showed good xanthine oxidase inhibitory activity for both substrates, hypoxanthine and xanthine. Six fractions were obtained from open column chromatography, and fraction E1 exhibited the best activity. The constituents of leaf essential oil and fraction E1 were analyzed by GC-MS. The main constituents of both leaf essential oil and fraction E1 were limonene and 3-carene; limonene showed a higher inhibitory effect on xanthine oxidase. Based on the enzyme kinetic investigation, limonene was the mixed-type inhibitor against xanthine oxidase. The results revealed that Pistacia chinensis leaf essential oil and limonene have the potential to act as natural remedies for the treatment of gout.